Neuromarketing - An Opportunity or a Threat? Neuromarketing - An Opportunity or a Threat? - Nadanyiova, Margareta (Communications - Scientific letters of the University of Zilina, 2017)
The reason of neuromarketing use lies in an attempt to understand consumer behaviour and motivation to make a purchase of certain product. This method is based on the assumption that the purchase decisions is largely influenced by emotions. The paper explains the essence of neuromarketing and selected neuromarketing technologies, such as Functional magnetic resonance imaging (FMRI), Electroencephalography (EEG) and Eye tracking. In this way, as a literature review, it provides a comparison of the views of several experts on the issue. An important part of the paper is to analyse the perception of neuromarketing by the professional and general public, which points to the advantages and disadvantages of its application. Accordingly, it is possible to summarize the benefits of using the results of neuromarketing research for companies that includes better understanding of customers, their loyalty, in order to strengthen their image and brand value.